PENINGKATAN LITERASI ANAK ANAK MELALUI PENDIRIAN PERPUSTAKAN MINI DAN KEGIATAN MEMBACA DI DESA LAU GUMBA KECAMATAN BERASTAGI KABUPATEN KARO - Febrika Dwi Lestari; Harjono Barasa; Rohayana Sormin; Ester Nainggolan; Amorianda Simbolon (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This community service discusses improving children's reading literacy through the establishment of a mini library and reading activities in Lau Gumba village, Berastagi sub-district, Karo district. Reading literacy is a form of ability to obtain, understand and use information from various sources in digital form. Reading literacy is not only related to knowledge and skills but also related to motivation, attitude, and behavior. This literacy itself in the context of education plays a role in developing a person's knowledge of certain subject matter and encouraging curiosity and developing creativity. To encourage children's reading literacy, a mini library was established that makes it easier for children to access the window of the world. The mini library facilitates learning and literacy activities. The provision of reading books should be efficient, meaning that it is appropriate to age and genre so that it meets the needs of readers. An interesting collection of educational reading books will increase children's interest in reading so that they want to visit the mini library continuously.